Drug interactions and risk of acute bleeding leading to hospitalisation or death in patients with chronic atrial fibrillation treated with warfarin - Gasse, Christiane; Hollowell, Jennifer; Meier, Christoph; Haefeli, Walter E. (Thrombosis and haemostasis, 2005)
Although drug interactions with warfarin are an important cause of excessive anticoagulation, their impact on the risk of serious bleeding is unknown. We therefore performed a cohort study and a nested case-control analysis to determine the risk of serious bleeding in 4152 patients (aged 40-84 years) with nonvalvular atrial fibrillation (AF) taking long-term warfarin (>3 months). The study population was drawn from the UK General Practice Research Database. More than half (58%) of eligible patients used potentially interacting drugs during continuous warfarin treatment. Among 45 identified cases of incident idiopathic bleeds (resulting in hospitalisation within 30 days or death within 7 days) and 143 matched controls, more cases than controls took ≥1 potentially interacting drug within the preceding 30 days (62.2% vs. 35.7%) and used >4 drugs (polypharmacy) within the preceding 90 days (80.0% vs. 66.4%). Conditional logistic regression analysis yielded an odds ratio (OR) of 3.4 (95% confidence interval [CI]: 1.4-8.5) for the risk of serious bleeding in patients treated with warfarin and ≥1 drugs potentially increasing the effect of warfarin vs. warfarin alone adjusted for polypharmacy, diabetes, hypertension, heart failure, and thyroid disease; the adjusted OR for the combined use of warfarin and aspirin vs. warfarin alone was 4.5 (95% CI: 1.1-18.1). We conclude that concurrent use of potentially interacting drugs with warfarin is associated with a 3 to 4.5-fold increased risk of serious bleeding in long-term warfarin users.
Online: 07. Dezember 2017
Gesehen am 18.05.2021